2016
DOI: 10.1097/mjt.0000000000000068
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Pain and Inflammation Associated With Chronic Low Back Pain With the Use of the Medical Food Theramine

Abstract: Management of chronic back pain is a challenge for physicians. Although standard treatments exert a modest effect, they are associated with narcotic addiction and serious side effects from nonsteroidal antiinflammatory agents. Moreover, neurotransmitter depletion from both the pain syndrome and therapy may contribute to a poor treatment outcome. Neurotransmitter deficiency may be related both to increased turnover rate and inadequate neurotransmitter precursors from the diet, particularly for essential and sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…For the sake of producing energy under the stress environment, tryptophan may resolve into carbohydrates. In chronic pain syndrome, the tryptophan level was substantially decreased before analgesic treatment and increased after the therapy (Shell et al, 2014). In addition, a previous study showed that neural injury increased the production of monoamine by aromatic L-amino acid decarboxylase (Wienecke et al, 2014).…”
Section: Tryptophan Metabolismmentioning
confidence: 95%
See 1 more Smart Citation
“…For the sake of producing energy under the stress environment, tryptophan may resolve into carbohydrates. In chronic pain syndrome, the tryptophan level was substantially decreased before analgesic treatment and increased after the therapy (Shell et al, 2014). In addition, a previous study showed that neural injury increased the production of monoamine by aromatic L-amino acid decarboxylase (Wienecke et al, 2014).…”
Section: Tryptophan Metabolismmentioning
confidence: 95%
“…In chronic pain syndrome, the tryptophan level was substantially decreased before analgesic treatment and increased after the therapy (Shell et al, 2014). For the sake of producing energy under the stress environment, tryptophan may resolve into carbohydrates.…”
Section: Tryptophan Metabolismmentioning
confidence: 99%
“…Of all pain categories defined most recently by the European Pain Federation [ 1 ], most trials referred to chronic musculoskeletal pain, i.e., low back pain (4 trials) [ 52 , 55 , 64 , 68 ], knee osteoarthritis in obese patients (3 trials) [ 44 , 46 , 74 ], fibromyalgia (7 trials) [ 45 , 47 , 56 , 59 , 61 , 62 , 78 ], neck pain and stiffness (1 trial) [ 79 ], musculoskeletal pain or peripheral neuropathy due to cancer treatment (3 trials) [ 64 , 69 , 70 ], chronic headache or migraine (6 trials) [ 43 , 48 , 49 , 51 , 66 , 67 ], generalized chronic musculoskeletal pain (2 trials) [ 54 , 72 ], diabetic neuropathy [ 50 , 71 ], taxol-induced neuropathic pain [ 63 ], or abdominal pain (10 trials) [ 53 , 57 , 58 , 60 , 65 , 71 , 73 , 75 , 76 , 77 , 80 ]. A synthesis is provided in Table 2 ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both indexes significantly improved after 28 days in the AAB and combination groups compared to ibuprofen alone, while serum levels of serine, histidine, arginine, and tryptophan increased to normal values after treatment, being directly correlated with treatment response. The substantial clinical improvement in the quality of chronic back pain was also accompanied by reduction in biomarkers of inflammation [55].…”
Section: High-protein Dietmentioning
confidence: 95%
“…Caloric restriction has been associated with a reduction of pain in rodents [ 618 , 619 ]. A change in amino acid composition has also been useful in low back pain patients [ 620 ], although a normalization of lowered amino acid levels was observed. A dietary intervention also improved chronic pancreatitis, again with a mixed effect on plasma amino acid levels [ 621 ].…”
Section: Mediators and Antagonists Acting On Sensory Neuronsmentioning
confidence: 99%